Expression and importance of matrix metalloproteinase 2 and 9 (MMP-2 and -9) in human trophoblast invasion - Gabarin Diana; Goldman Shlomit; Staun-Ram Elsebeth; Shalev Eliezer (BMC, 2004)
Abstract Background The aim of this study was to examine the invasiveness of first trimester trophoblasts according to the secretion profile of MMP-2 and -9 at different gestational stages, and to test the similarity between primary trophoblast cell-culture and the JAR choriocarcinoma cell-line. Methods First trimester trophoblasts were divided into two groups: 6-8 weeks (early) and 9-12 w (late) of gestation. The two trophoblast groups and JAR cells were cultured in medium, with various concentrations of forskolin and Epidermal Growth Factor (EGF). Proteolytic activity was detected by zymography and invasiveness was assessed by Matrigel invasion assay. Student's T-test was used for statistical analysis. Results In 6-8 w trophoblast, proMMP-2 was only slightly dominant over proMMP-9 (53.2% vs. 46.8% respectively), whereas in 9-12 w, proMMP-9 was clearly dominant over proMMP-2 (61.7% vs.38.3% respectively). In JAR cells proMMP-2 was strongly dominant (90.2% vs.9.8% respectively). In JAR cells forskolin significantly increased proMMP-2 and -9 secretion (128.5% +/- 12 and 183.2% +/- 27.9 of control, respectively). EGF had a dual effect on JAR cells: at 8 ng/ml both proMMP-2 and -9 were increased (133.5% +/-15 and 223.9% +/- 32.4 of control, respectively) while at 80 ng/ml both proMMP-2 and -9 were decreased (65.1% +/- 18.3 and 66.6% +/- 37 of control, respectively). Forskolin significantly increased both proMMP-2 and -9 secretion in 6-8 w and 9-12 w trophoblasts (125.9% +/- 6.3,128.4% +/- 6.4; 169.7% +/- 20.3, 120.3% +/- 4.5 of control, respectively). EGF also significantly increased both proMMP-2 and -9 secretion in 6-8 w and 9-12 w trophoblasts (141.22% +/- 14.8, 138.8% +/- 10.3; 168.3% +/- 18.2, 117.3 +/- 3.8 of control, respectively). Both forskolin and EGF increased trophoblast cells invasiveness in all groups. The invasive ability of trophoblast cells, induced by forskolin, was reduced by MMP-2 antibody in: JAR cells, 6-8 w and 9-12 w trophoblasts. Likewise trophoblast invasion induced by EGF was reduced by MMP-2 antibody in all groups. However the invasive ability induced by forskolin or EGF was inhibited by MMP-9 antibody only in trophoblasts from 9-12 w. Conclusions First trimester trophoblasts express differential gelatinase secretion profile according to the gestational week. In JAR and early trophoblasts (6-8 w) MMP-2 is the main gelatinase and the key enzyme in trophoblast invasion. Thereafter in late first trimester trophoblasts (9-12 w), both MMP-2 and -9 participate in trophoblast invasion.